STUDI POTENSI SUMBER-SUMBER PENDANAAN PENINGKATAN KAPASITAS YANG BERKELANJUTAN PADA PEMERINTAH KABUPATEN TAPANULI TENGAH - Sihombing, Binsar (UNIKA Santo Thomas, 2010)
Study Potential Sources Of Funding Sustainable Capacity Building in Central Tapanuli the ï¬nancial activities related to the capacity of the funding process. This study will address issues of potential sources of finding local government capacitybuilding and prediction if local revenue sources based on the potential of Central Tapanuli. This study aims to determine and analyze the relationship of GDP to the sources of local revenues, which are used as guidelines for sustainable capacity building ï¬mding. This study is intended to be the sources of funding capacity can be estimated from the period 2010-2015.